RANCANG BANGUN SISTEM AKUNTANSI PENJUALAN DAN PENERIMAAN KAS PADA CV SONO PUTRO DELANGGU - Ihsan Adi Nugraha, Suharno & Djoko Kristianto (Universitas Slamet Riyadi, 2017)
Sales are a major source of income, while the cash receipts are the mainsource of cash from operating activities. The purpose of this study to determinewhether the accounting system sales and cash receipts are applied by CV Sono PutroDelanggu been effective so as to support the internal control of sales and cashreceipts and designing wake accounting system sales and cash receipts to boost theeffectiveness of internal controls on CV Sono Putro Delanggu. The type of data usedquantitative and data qualitative. Data source of primary data. Data collectiontechniques with interviews, documentation, observation, and questionnaires. Theresults of sales system is the absence of a record on a card receivables, credit is notauthorized by the credit function, mail order delivery order and use theresponsibilities of the sales function yet, no separate sales function with a creditfunction, there is no separation between the functions of sales and treasury functions,director of the company is still involved in receiving orders from customers. Theresults of cash receipts system is no separation of functions treasury and accountingfunctions, the absence of separation of functions of cash receipts and accountingfunctions, not insured collectors and cashiers, cash is in the hands of collectorsjourney as they are not insured by the company, cash receipts from buyers in theauthorization by the sales function.Keywords: sale systems, cash receipt system, internal control system.